2008
DOI: 10.1103/physrevd.77.124020
|View full text |Cite
|
Sign up to set email alerts
|

Post-Newtonian parameters in the tensor-vector-scalar theory

Abstract: We investigate post-Newtonian parameters in the tensor-vector-scalar (TeVeS) theory in a general setting while previous researches have been restricted to spherically symmetric cases. Based on the assumption that both the physical and Einstein metrics have Minkowski metric at the zeroth order, we show γ = 1 as in the previous researches. We find two remarkable things for other parameters. The first is the value β = 1 while it has been reported that β = 1 for the case when the vector field is not purely timelik… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Although the above constraints on classical MOND models are useful guides, proper constraints can thus only truly be set on the various relativistic theories presented in Sect. 7, the first order constraints on these theories coming from their own post-newtonian parameters [66,100,174,373,391,451]. What is more, and makes all these tests perhaps unnecessary, it has recently been shown that it was possible to cancel any deviation from General Relativity at small distances in most of these relativistic theories, independently of the form of the µ-function [22].…”
Section: Mond In the Solar Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the above constraints on classical MOND models are useful guides, proper constraints can thus only truly be set on the various relativistic theories presented in Sect. 7, the first order constraints on these theories coming from their own post-newtonian parameters [66,100,174,373,391,451]. What is more, and makes all these tests perhaps unnecessary, it has recently been shown that it was possible to cancel any deviation from General Relativity at small distances in most of these relativistic theories, independently of the form of the µ-function [22].…”
Section: Mond In the Solar Systemmentioning
confidence: 99%
“…The relations between this free function and Milgrom's µ can be found in [146,432] (see also Sect. 6.2), 49 Expressed in terms of Uµ and its congugate momenta P µ = ∂L/∂Uµ the detailed structure of null and timelike geodesics of the theory in [432], the analysis of the parametrized post-Newtonian coefficients (including the preferred-frame parameters quantifying the local breaking of Lorentz invariance) in [174,373,391,451], solutions for black holes and neutron stars in [245,246,248,247,375,439,440], and gravitational waves in [217,215,216,374]. It is important to remember that TeVeS is not equivalent to GR in the strong regime, which is why it can be tested there, e.g.…”
Section: Generalized Tensor-vector-scalar Theorymentioning
confidence: 99%
“…In recent years, such options are carefully investigated in literature. Alternative gravity theories based on the modification of Einstein-Hilbert action include f (R) gravity [14][15][16][17], scalar-tensor gravity [18][19][20] and Lovelock gravity [21,22], to name a few. Similarly there are models in which only the matter term is modified, examples are Cardassian model [23][24][25], the bulk viscous stress [26][27][28] and the anisotropic stress [29].…”
Section: Introductionmentioning
confidence: 99%
“…Various astrophysical and cosmological phenomena exhibit observable signatures of TeVeS [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. TeVeS is essentially a bi-metrical gravitational theory where matter and gravity are distinguished by the metric fields they operate with.…”
Section: Teves Gravitymentioning
confidence: 99%